PENGARUH POLA PELATIH KOOPERATIF TERHADAP MOTIVASI BERPRESTASI ATLET BOLABASKET PUTRA SMA 17 AGUSTUS 1945 SURABAYA - Darisman, Eka Kurnia (Gelora : Jurnal Pendidikan Olahraga dan Kesehatan IKIP Mataram, 2016)
Psychology Student comprehension in education is important for teachers. To achieve the goals of training and achieve the desired performance, the coach must realize that the improvement of athlete achievement is related to the personal development of the athlete concerned. Many people disagree that this coaching style has an influence on the athlete’s training process. The pattern of coaches can affect the achievements they will achieve. The purpose of this study was to determine the effect of the cooperative coach pattern on the achievement motivation of basketball athletes in SMA 17 August 1945 Surabaya. This study used a pre-experimental design. The population is the extracurricular participants of SMA 17 August 1945 Surabaya with a total sample of 15 people. The measurement test on each variable uses a closed questionnaire that has been tested for validity and reliability. The results in this study show that achievement motivation and cooperative trainer patterns are on a linear graph. Then it was also found that there was a strong and significant positive relationship of 0.714. From the results of this study indicate that 50.98% of basketball athletes outra SMA 17 August 1945 Surabaya achievement motivation is influenced by the pattern of cooperative coaches